Gema Duta: Experimental Musical Works | Gema Duta: Karya Musik Eksperimental - I Kadek Endra Dwi Antara; Putu Tiodore Adi Bawa (GHURNITA: Jurnal Seni Karawitan, 2024)
Gema Duta is an experimental musical work that emphasizes the simplicity of instruments and musical formulas, mainly focusing on using Gong and Bumbung Pipa as the primary media. This work was born from the artist's desire to give space to the unique characteristics of the Gong and Bumbung Pipa, understanding their existence as more than just sound resonators. Musically, Gema Duta carries a simple approach inspired by minimal instrumentation. The creation process involved stages of exploration and experimentation, mainly rooted in previous experiences with Balinese Gamelan, where similar patterns did not fit due to differences in the sound character of the instruments. Therefore, the arranger chose to compose simple music according to the instruments' characteristics. Gema Duta takes inspiration from acoustic defects produced by sound reflection on a delayed surface, creating a sound different from the original sound source, "Echoes" or "echoes."